Free vibration of laminated and FGM/CNT composites annular thick plates with shear deformation by discrete singular convolution method. (15th February 2018) - Mercan, Kadir; Baltacıoglu, Ali Kemal; Civalek, Ömer
Abstract: Free vibration analysis of laminated composite and functionally graded materials (FGM) composite annular plates is investigated. The equations of motion of annular plates have been obtained via conical shell equations. Shear deformation theory is used for shell equation of motion. After the implementation of the Regularized Shannon delta (RSD) kernel and Lagrange delta sequence (LDS) kernel, the method of discrete singular convolution (DSC) is used for numerical solution of the governing equations to obtain the frequency values. To verify the accuracy of this method, comparisons of the present results are made with results available in the open literature. Some parametric results for annular plates and conical panels have depicted for isotropic, laminated composite and functionally graded composite materials. It is found that the convergence and accuracy of the present DSC method is very good for vibration problem of annular plates with functionally graded materials (FMG) and laminated composite cases. Some results about carbon nanotube reinforced (CNTR) composite plate have also been approved.